Packaging techniques of photonic integrated circuits for PON networks - Ferreira, Alexandre Pontes (2019)
The optic communications are more and more present in our day-to-day lives. With the increase of the connected devices to the internet, there is an urge of a great capacity e efficiency in data transmission. Due to this evolution it is necessary to improve device performance. This assignment focuses on thermal, electric and optic encapsulation, where through a Photonic Integrated Circuit (PIC), entitled \Case Study", a XFP transceiver demonstrator the used integrated optic. The first phase the rules for an optic and electric encapsulation were addressed, as well as, the active and passive alignments techniques of an PIC. Subsequently, had been made electric viability tests of a PIC where it has been tested with a distributed feedback laser at high temperatures. Afterward it was done thermic control tests to the system, where the temperature sensors integrated in the holder have been characterized of gold and platinum. At last, it was done a prototype a XFP transceiver demonstrator, used a PIC transceiver assembled onto the Silicon (Si)-holder with a Thermoelectric Cooler (TEC) attached directly on the holder bottom surface, approaching all the progression processes of this same prototype.